PENGGUNAAN METODE MABAC PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LOKASI MAGANG TERBAIK - Safitri, Nina; Bangun, Budianto; Sihombing, Volvo (Politeknik Bisnis Indonesia, 2024)
This study aims to develop a Decision Support System (DSS) based on the Multiple Attribute Boundary Approximation Area Comparison (MABAC) method to assist Labuhan Batu University students in choosing the best internship location. The main problem faced is the difficulty in determining a strategic and quality internship location due to limited resources. This study uses a quantitative descriptive method involving five main criteria: Location Distance, Company Reputation, Facilities, Suitability of the Internship Program with the Curriculum, and Work Environment. Data were collected through literature, expert consultation, and primary and secondary data analysis. Based on the results of data processing using the MABAC method in this study, 3 best internship locations were obtained, namely locations A9, A4, and A3. The results of the analysis using the MABAC method show the system's ability to provide internship location recommendations based on objective multicriteria assessments. The resulting system can help make it easier for students to choose an internship location that suits their needs.